Fundamentals properties of soft clay/ Mohamad Fauzi Ramli - Ramli, Mohamad Fauzi (1993)
This research project is aimed at studying the properties of soft clay. Soil Classification test was performed on disturbed samples and Triaxial Undrained test on undisturbed samples. All laboratory test were conducted in accordance to BS 1377:1990. The specimens of soft clay used were taken from different boreholes at the same- site and the range of depth between A.5- - p.5 meter. The samples of soft clay were given by Jabatan Pengairan dan Saliran, Jalan Ampang, in connection with soil investigation at Sungai Besar, Sabak Bernam. The experimental results indicated that the parameters and properties of the soft clay varies from place to place and the moisture content are mostly over 100% for undisturbed samples. In addition, this soft clay can be classified to be of very high plasticity and high compressibility.